FGFR2 gene polymorphism rs2981582 is associated with non-functioning pituitary adenomas in Chinese Han population: a case–control study. Issue 6 (9th November 2018) - Zhu, Bin; Wang, Juan; Qin, Lingling; Wang, Lei; Zheng, Yanfei; Zhang, Lei; Wang, Wei
Abstract : The association of the fibroblast growth factor receptor 2 gene ( FGFR2 ) polymorphism rs2981582 with breast cancer has been extensively studied, whereas the role of this polymorphism in non-functioning pituitary adenoma (NFPA) has not been elucidated. We thus investigated a potential association of rs2981582 with NFPA. A total of 79 patients and 142 healthy control participants were enrolled in our study. DNA of the participants was extracted from peripheral blood samples and genotyped by using the MassARRAY method. We found that the AA genotype was associated with a higher risk of developing NFPA (OR = 1.743, 95%CI: 1.151–2.64, P =0.008). After adjusting for risk factors, significant difference was still observed between the two groups (OR = 1.862, 95%CI: 1.172–2.957, P =0.008). Moreover, under the assumptions of the recessive model (OR = 3.051, 95%CI: 1.403–6.635, P =0.005) and the additive model (AG: OR = 0.329, 95%CI: 0.144–0.755, P =0.009; AA: OR = 0.326, 95%CI: 0.141–0.757, P =0.009), rs2981582 was associated with an increased risk of NFPA. Our results proved that FGFR2 rs2981582 AA genotype was associated with a higher risk of NFPA. The recessive model and additive model also showed increased the risk of NFPA.